Human seroprevalence of Toscana virus and Sicilian phlebovirus in the southwest of Portugal - Maia, Carla (2022)
Funding Information: Fundação para a Ciência e a Tecnologia, I.P. (FCT) for funding through contract GHTM-UID/Multi/04413/2013 and Investigator Starting Grant IF/01302/2015. AP was supported by the Portuguese Ministry of Education and Science (via FCT) through a PhD grant (SFRH/BD/116516/2016). Publisher Copyright: © 2021, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.